Recursive Polynomial Reductions for Classical Planning - Tozicka, Jan; Jakubuv, Jan; Svatos, Martin; Komenda, Antonin (Proceedings of the International Conference on Automated Planning and Scheduling, 2016)
Reducing accidental complexity in planning problems is a well-established method for increasing efficiency of classical planning. Removal of superfluous facts and actions, and problem transformation by recursive macro actions are representatives of such methods working directly on input planning problems. Despite of its general applicability and thorough theoretical analysis, there is only a sparse amount of experimental results. In this paper, we adopt selected reduction methods from literature and amend them with a generalization-based reduction scheme and auxiliary reductions. We show that all presented reductions are polynomial in time to the size of an input problem. All reductions applied in a recursive manner produce only safe (solution preserving) abstractions of the problem, and they can implicitly represent exponentially long plans in a compact form. Experimentally, we validate efficiency of the presented reductions on the IPC benchmark set and show average 24% reduction over all problems. Additionally, we experimentally analyze the trade-off between increase of coverage and decrease of the plan quality.